Transcriptional regulation of neutrophil differentiation and function during inflammation - Ai, Z; Udalova, IA (Wiley, 2020)
Neutrophils are the most abundant leukocytes in innate immunity where they elicit powerful effector functions to eliminate invading pathogens and modulate the adaptive as well as the innate immune response. Neutrophil function must be tightly regulated during inflammation and infection to avoid additional tissue damage. Increasing evidence suggests that transcription factors (TFs) function as key regulators to modulate transcriptional output, thereby controlling cell fate decision and the inflammatory responses. However, the molecular mechanisms underlying neutrophil differentiation and function during inflammation remain largely uncharacterized. Here, we provide a comprehensive overview of TFs known to be crucial for neutrophil maturation and in the signaling pathways that control neutrophil differentiation and activation. We also outline how emerging genomic and single-cell technologies may facilitate further discovery of neutrophil transcriptional regulators.